Thin Capitalization and Dividend Policy on Tax Avoidance: The Moderating Role of Managerial Ownership: Kapitalisasi Tipis dan Kebijakan Dividen terhadap Penghindaran Pajak: Peran Moderasi Kepemilikan Manajerial - Nurlinda Hermini; Restu Alpiansah; Susilo Talidobel; Wira Hendri; Stevany Hanalyna Dethan (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The phenomenon of tax avoidance in Indonesia remains a serious challenge, with losses amounting to US$4.86 billion per year. Although tax revenue often meets its estimated targets, Indonesia’s tax-to-GDP ratio is still low compared to several other ASEAN countries. Companies tend to view taxes as a burden to be paid and use legal tax avoidance strategies to reduce payments. This associative quantitative research analyzes the influence of thin capitalization and dividend policy on tax avoidance, with managerial ownership as a moderator. The data used is secondary data obtain from the financial statements and annual reports of 12 non-financial companies consistently listed in the LQ45 index on the Indonesia Stock Exchange for the period 2020-2023. The analysis technique uses panel data regression with the Common Effect Model (CEM), processed thru EViews 12 software. The test results show that thin capitalization and dividend policy do not have a significant effect on tax avoidance. Similarly, managerial ownership was unable to moderate the influence of both thin capitalization and dividend policy on tax avoidance.